(untitled) (International Journal of Engineering and Computer Science, 2017)
One of the main considerations in designing routing protocols for Mobile Ad -Hoc Network (MANET) is to increase network lifetime by minimizing nodes’ energy consumption, since nodes are typically battery powered. Many proposals have been addressed to this problem; however, few papers consider a proactive protocol like Optimized Link State Routing Protocol (OLSR) to better manage the energy consumption. Some of them have explored modifications to the MPRs selection mechanism, whereas others have investigated multiple cross layer parameters to increase the network lifetime. In this paper, we explored both modification to MPR selection and integrating appropriate routing metrics in the routing decision scheme to lessen effects of reason that lead to more energy consumption. Our power-aware version of OLSR is proven by simulations in NS3 under a range of different mobile scenarios. Significant performance gains of 20% are obtained in network lifetime for our modified OLSR and little to no performance gains in term of Packet Delivery Ratio (PDR).